1993
DOI: 10.1021/ma00053a024
|View full text |Cite
|
Sign up to set email alerts
|

Side-chain liquid crystalline poly(N-maleimides). 5. Dielectric relaxation behavior of liquid crystalline side-chain and amorphous poly(N-maleimides). A comparative structural study

Abstract: A series of five nonaligned comblike polyUV-maleimides) have been studied by frequency (200 Hz-100 kHz) and temperature (from 123 to 423 K) dependent dielectric measurements. Three of them are smectic side-chain liquid crystal polymers (SCLCPs) and the other two are amorphous materials. These samples also allow us to study the possible influence of the smectic field. By a change of the chemical nature of the structure of mesogens, a self-consistent assignment of the different relaxational processes has been po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0
2

Year Published

1995
1995
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 16 publications
3
31
0
2
Order By: Relevance
“…1 a, b), caractéristique des polymères cristaux liquides à groupements pendants fortement polaires (Kresse et al 23,24) , Krupicka et al 34) , Hsiue et al 20) ). Quand l'espaceur est trop court 17) ). Le mécanisme de cette relaxation d consiste en une rotation du groupement latéral autour de la chaîne principale.…”
Section: Résultats Et Discussionunclassified
See 1 more Smart Citation
“…1 a, b), caractéristique des polymères cristaux liquides à groupements pendants fortement polaires (Kresse et al 23,24) , Krupicka et al 34) , Hsiue et al 20) ). Quand l'espaceur est trop court 17) ). Le mécanisme de cette relaxation d consiste en une rotation du groupement latéral autour de la chaîne principale.…”
Section: Résultats Et Discussionunclassified
“…De nombreux travaux ont été réalisés ou sont encore effectués sur la caractérisation des propriétés diélectri-ques des polymères cristaux liquides à groupements pendants (Attard et al 14) , Bormuth et al 15) , Zhong et al 16) , Romero Colomer et al 17) , Kim et al 18) , Akins et al 19) , Hsiue et al 20) ). Ces polymères permettent par vitrification d'obtenir des mésophases solides.…”
Section: Introductionunclassified
“…[15][16][17] In the first example, poly-and copolymaleimides, in which the cholesteroxycarbonyl mesogenic group was attached to the polymer backbone through a paraffinic spacer containing one, 15 5, or 11 methylenic units, 16 were synthesized and investigated for their chirooptical properties. It was shown that asymmetric induction polymerization took place in all the investigated systems.…”
Section: Introductionmentioning
confidence: 99%
“…The second SCLC polymaleimide series is based on phenylbenzoate mesogenic groups attached to the backbone through 10 methylenic units. 17 These polymaleimides exhibit smectic phases.…”
Section: Introductionmentioning
confidence: 99%
“…-relaxation: This relaxation process is neither present in the common polymethacrylates nor in corresponding liquid crystalline materials. Only for poly(N-maleimides) with two ester linkages and a range of mesogenic units two b -processes are described 3,32) . For the investigated polymers the b…”
mentioning
confidence: 99%